Clinical characteristic–assisted surgical benefit stratification for resection of primary tumor in patients with advanced primary malignant bone neoplasms: a population-based propensity score–matched analysis - Tong, Yuexin; Jiang, Liming; Cui, Yuekai; Pi, Yangwei; Gong, Yan; Zhao, Dongxu (Frontiers in Oncology, 2023)
Background: Primary tumor resection (PTR) is the standard treatment for patients with primary malignant bone neoplasms (PMBNs). This study aimed to develop a prediction model to estimate the beneficial probability of PTR for this population. Methods: This study extracted data from patients diagnosed with advanced PMBNs, as recorded in the Surveillance, Epidemiology and End Results (SEER) database, with the period of 2004 to 2015. The patient cohort was then bifurcated into two groups, those who underwent surgical procedures and the non-surgery group. Propensity score matching (PSM) was utilized to mitigate any confounding factors in the study. Moreover, the study used this method to assess the capacity of the nomogram to distinguish patients likely to derive benefits from surgical intervention. The study was grounded in the hypothesis that patients who underwent PTR and survived beyond the median overall survival (OS) time would potentially benefit from the surgery. Subsequently, logistic regression analysis was performed to asecertain significant predictors, facilitating the development of a nomogram. Results: The SEER database provided a total of 839 eligible patients for the study, among which 536 (63.9%) underwent PTR. Following a 2:1 PSM analysis, patients were classified into two groups: 364 patients in the surgery group and 182 patients in the non-surgery group. Crucial factors such as age, M stage and tumor size were identified to be significantly correlated with surgical benefits in patients with advanced PMBNs. Subsequently, a nomogram was developed that uses these independent predictors. The validation of this predictive model confirmed its high accuracy and excellent discrimination ability of the nomogram to distinguish patients who would most likely benefit from surgical intervention. Conclusion: In this study, we devised a user-friendly nomogram to forecast the likelihood of surgical benefits for patients diagnosed with advanced PMBNs. This tool facilitates the identification of the most suitable candidates for PTR, thus promoting more discerning and effective use of surgical intervention in this patient population.